Parametric Earthquake Analysis of Thick Plates Using Mindlin’s Theory - Y.I. Özdemir; Y. Ayvaz (Shock and Vibration)
The purpose of this paper is to study parametric earthquake analysis of thick plates using Mindlin's theory, to determine the effects of the thickness/span ratio, the aspect ratio and the boundary conditions on the linear responses of thick plates subjected to earthquake excitations and to present the frequency parameters and the mode shapes of the same plates. In the analysis, finite element method is used for spatial integration and the Newmark-β method is used for time integration. A computer program using finite element method is coded in C++ to analyze the plates clamped or simply supported along all four edges. In the analysis, 8-noded finite element is used. Graphs and tables are presented that should help engineers in the design of thick plates subjected to earthquake excitations. It is concluded that, in general, the changes in the thickness/span ratio are more effective on the maximum responses considered in this study than the changes in the aspect ratio. It is also concluded that the effects of the change in the thickness/span ratio on the frequency parameter of the thick plates are always larger than those of the change in the aspect ratio.